1964
DOI: 10.1192/bjp.110.467.588
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Metabolism in States of Depression

Abstract: We have previously demonstrated, in small groups of patients receiving either electric convulsive treatments or imipramine therapy, changes in calcium metabolism associated with recovery from states of depression (5, 7). Other investigators have also reported somewhat unusual changes in calcium physiology among depressed patients or during the administration of antidepressant therapies. These include low cerebrospinal fluid calcium levels (4), changes in blood calcium during electric convulsive treatments (10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1968
1968
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In addition, changes in serum or CSF calcium levels have been reported in patients with depression not directly associated with endocrine dysfunction 32–40. Conversely, reduced plasma, serum, or CSF calcium levels accompany improvement of depressive symptomatology after either electroconvulsive shock or antidepressant drug treatment 33–35,39,41–43. Finally, calcium channel antagonists have been reported to be antidepressant in an anecdotal report 44,45…”
Section: Major Depression and Excitatory Amino Acidsmentioning
confidence: 99%
“…In addition, changes in serum or CSF calcium levels have been reported in patients with depression not directly associated with endocrine dysfunction 32–40. Conversely, reduced plasma, serum, or CSF calcium levels accompany improvement of depressive symptomatology after either electroconvulsive shock or antidepressant drug treatment 33–35,39,41–43. Finally, calcium channel antagonists have been reported to be antidepressant in an anecdotal report 44,45…”
Section: Major Depression and Excitatory Amino Acidsmentioning
confidence: 99%
“…While serum magnesium in manic-depressive patients does not seem to show any consistent changes (11)(12)(13)(14), urinary excretion was found to be increased during recovery form depression (15), in contrast to urinary calcium which was decreased during recovery from depression (5,6).…”
Section: Introductionmentioning
confidence: 96%
“…The possibility therefore exists that such an influence may have certain bearing on the effect of lithium in manic-depressive psychosis, because calcium is important both for the impulse propagation along the nerve cell (3) and for the synaptic transmission (4). Furthermore, calcium metabolism may be changed in manic-depressive patients (5,6), and changes in calcium metabolism are often accompanied by mental disturbances (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…As to calcium we found lower excretions after recovery than during depression, but the difference was not statistically significant. In the studies of Flach (1964), Fluch & Faragalla (1966, and Fischback (1971) a similar change in calcium excretion was found, and in all of the three the difference was highly significant. On the other hand, Coirault et al (1959) found just the opposite, i. e. an increase in urinary calcium during recovery from depression.…”
Section: Discussionmentioning
confidence: 58%